Stability and properties of liquid CO sub(2) at high pressure and high temperature: Implications for electrical conductivities in Earth's lower mantle - Wu, Min; Tse, John S; Pan, Yuanming (Geophysical research letters, 2015)
Carbon dioxide (CO sub(2)), one of the most important planetary materials, has been the subject of extensive experimental and theoretical studies. However, the stabilities and properties of CO sub(2) at high pressures and temperatures relevant to Earth's mantle and core remain controversial. We have studied the molten structures of CO sub(2)-V with first-principles molecular dynamic calculations at 60GPa and different temperatures. The formation of oxygen molecules in the melt is consistent with experimental observations. In particular, the melting transition is accompanying by metallization. The metallic behavior is shown to originate from electron delocalization between oxygen via the overlap of the pi orbitals from the dissociated oxygen-rich species. Metallic molten CO sub(2) is a potential candidate to explain the high conductivities of the Earth's lower mantle. Furthermore, theoretical results do not support the existence of the proposed ionic solid phase of CO sub(2) at high temperature and high pressure. Key Points * Dissociation of carbon dioxide at high pressure and high temperature * Metallization of carbon dioxide at high pressure and temperature * Molten CO sub(2) may be a contributing factor to the high conductivity of the Earth's mantle